Is the Antarctic Ophryotrocha orensanzi (Annelida: Dorvilleidae) a circumpolar non-specialized opportunist?. Issue 2 (4th March 2017) - Paxton, Hannelore; Wiklund, Helena; Alexander, Frances; Taboada, Sergi
Abstract : The dorvilleid polychaete Ophryotrocha orensanzi is reported from the vicinity of Casey station, East Antarctica, an astounding range extension from its previous records in the South Shetland Islands to the opposite side of the Antarctic continent, suggesting that it is a circumpolar species. Genetic studies confirmed the conspecificity and the inferred haplotype network suggests that the two populations studied are genetically connected. Morphological studies of the newly collected material revealed that the jaw apparatus consists of the P- and K-type, in accordance with other members of the 'lobifera' clade. We are reporting a previously undocumented button-like structure that we are referring to as 'nuchal papilla' for its association with the nuchal region, and present an emended diagnosis for the species. The Casey station population was collected in a clean, unpolluted intertidal environment associated with stones and seaweeds. We are challenging the generally held opinion that Ophryotrocha species are specialists of organically enriched substrates, suggesting that, at least for the particulars of O. orensanzi, they might also be unspecialized opportunists, able to exist in the most pristine environments and having the ability to rapidly increase their population sizes under favourable conditions.